Pertumbuhan dan produksi beberapa mutan kedelai Kipas Merah generasi ke lima di kebun percobaan Lampahan Bener Meriah - Fahmil Huda; Ainun Marliah; Erita Hayati; Hasanuddin; Zuyasna Zuyasna (Cassowary, 2021)
The research objective was to determine the growth and production of the fifth generation mutant soybean (M5) at the Lampahan Bener Meriah University Farm. This study used a non-factorial randomized block design (RBD) with three replications, where four genotypes of Kipas Merah mutants were tested and compared with Kipas Merah (their parents) and Grobogan variety (large seeds). The variables observed were plant height, number of branches, number of productive branches, days of flowering, number of pods, number of pithy pods, number of seeds, weight of seeds per plant and weight of 100 seeds. The results of this study indicate that the M5 mutant soybean genotype has no significant different on plant height at age 4, 6, 8 WAP, number of branches per plant aged 6, 8 WAP, number of pods, and number of productive branches per plant. The highest average plant height and the highest number of productive branches found in Kipas Merah (G0) varieties. Mutant soybean genotype M5 had a very significant effect on flowering age and seed weight per plot. The fastest flowering was Kipas Merah (G0) and the latest flowering was A11 (G4) and A14 (G5) mutants. The highest weight of 100 seeds found in mutant A11 (G4) about 18.585 g and no significant different with Grobogan variety (18.827 g). The highest seed weight per plot found in mutant A11 (G4) about 169.35g. Based on the results of this study, mutant A11 (G4) was the best growth and production of the tested M5 genotypes.